2014
DOI: 10.1002/jmr.2399
|View full text |Cite
|
Sign up to set email alerts
|

Force‐induced globule–coil transition in laminin binding protein and its role for viral–cell membrane fusion

Abstract: The specific interactions of the pairs laminin binding protein (LBP)-purified tick-borne encephalitis viral surface protein E and certain recombinant fragments of this protein, as well as West Nile viral surface protein E and certain recombinant fragments of that protein, are studied by combined methods of single-molecule dynamic force spectroscopy (SMDFS), enzyme immunoassay and optical surface waves-based biosensor measurements. The experiments were performed at neutral pH (7.4) and acid pH (5.3) conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…It was found that it was proteolysis of extracellular matrix proteins with serine protease from mosquito saliva that increased viral attachment to heparan sulfate proteoglycans, thereby augmenting dengue virus infectivity in vitro [119] . In addition, three proteins from the ECM proteoglycans pathway (integrin subunit beta encoded by ITGB3, laminin subunits beta 1 and beta 2 encoded by LAMB1 and LAMB2) can interact physically with the whole TBEV particle or with its proteins [69, 72, 120].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that it was proteolysis of extracellular matrix proteins with serine protease from mosquito saliva that increased viral attachment to heparan sulfate proteoglycans, thereby augmenting dengue virus infectivity in vitro [119] . In addition, three proteins from the ECM proteoglycans pathway (integrin subunit beta encoded by ITGB3, laminin subunits beta 1 and beta 2 encoded by LAMB1 and LAMB2) can interact physically with the whole TBEV particle or with its proteins [69, 72, 120].…”
Section: Discussionmentioning
confidence: 99%
“…The entry process of flaviviruses occurs mainly via receptor-mediated endocytosis, but entry via micropinocytosis is also possible [ 58 , 59 , 60 ]. There are two major receptor candidates for TBEV in mammalian cells, laminin-binding protein (LBP) and the αVβ3 integrin but no receptor candidates in tick cells have been identified so far [ 61 , 62 , 63 ]. Studies using anti-idiotypic antibodies suggested that there could be other receptor candidates of as yet unknown identity [ 61 , 64 , 65 ].…”
Section: Life Cyclementioning
confidence: 99%
“…WNV attaches to host cells through the interaction of the viral E protein and cellular receptors on the surface of host cells (Fields et al, 2013). Several attachment receptors of WNV have been reported and include the laminin receptor (Bogachek et al, 2010;Perera-Lecoin et al, 2014;Zaitsev et al, 2014;Zidane et al, 2013), TIM (T cell/transmembrane, immunoglobulin and mucin) and TAM (Tyro3, Axl and Mer) families (Carnec et al, 2016;Morizono and Chen, 2014;Perera-Lecoin et al, 2014), DC-SIGN/L-SIGN (dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin) (Davis et al, 2006;Denizot et al, 2012;Martina et al, 2008;Shimojima et al, 2014) and integrin ␣v␤3 (Bogachek et al, 2010;Fields et al, 2013;Perera-Lecoin et al, 2014;Smit et al, 2011;Zaitsev et al, 2014). Following attachment, the virus is then internalized into the cytoplasm via clathrin-mediated endocytosis (Brinton, 2014;Chu and Ng, 2004;Fields et al, 2013).…”
Section: Introductionmentioning
confidence: 99%